2001
DOI: 10.1002/1097-0029(20010301)52:5<541::aid-jemt1039>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Searching for specific binding sites of the secretory glycoproteins of the subcommissural organ

Abstract: The molecular organization of Reissner's fiber (RF), the structure of its proteins, and the permanent turnover of these proteins are all facts supporting the possibility that RF may perform multiple functions. There is evidence that CSF-soluble RF-glycoproteins may occur under physiological conditions. The present investigation was designed to investigate the probable existence within the CNS of specific binding sites for RF-glycoproteins. Three experimental protocols were used: (1) immunocytochemistry of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2004
2004
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
8
0
1
Order By: Relevance
“…The SCO may also regulate CSF formation. Receptors for SCO glycoproteins are found on the choroid plexus (Miranda et al, 2001), suggesting that CSF production could be influenced by SCO activity. It would be interesting to determine whether any of these parameters are altered in Ro1 mice.…”
Section: Discussionmentioning
confidence: 99%
“…The SCO may also regulate CSF formation. Receptors for SCO glycoproteins are found on the choroid plexus (Miranda et al, 2001), suggesting that CSF production could be influenced by SCO activity. It would be interesting to determine whether any of these parameters are altered in Ro1 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the presence of binding sites for RF glycoproteins in the PVT has been demonstrated (Miranda et al, 2001). These results suggest that the dysfunctional secretory SCO of homozygotes is related to these neurohistological disorders, especially because the PVT does not express the Msx1 gene in normal conditions (or in KO mice).…”
Section: Subcommissural Organ May Be Involved In Posterior Commissurementioning
confidence: 99%
“…Msx1 mutant mice displayed neither structural nor ultrastructural anomalies in the choroidal cells, nor in the tela choroidea (results not shown). However, alterations of the secretory activity or cerebrospinal fluid (CSF) reabsorption cannot be ruled out, taking into account (1) the strong Msx1 expression in these structures and the presence of specific binding sites for Reissner's fiber-glycoproteins in ependymal cells of the choroid plexus (Miranda et al, 2001), and (2) the ependymal detachment, which seems to be, in certain cases, the primary cause of hydrocephalus .…”
Section: Msx1 Deficient Mice Display a Severe Hydrocephalusmentioning
confidence: 99%
“…Hence, if floor plate and choroid plexus cells do not synthesize and release the apical AFRU-positive material, a specific binding of such glycoproteins to these cells might be suggested. Furthermore, Miranda et al (2001) have reported the binding of radiolabelled RF glycoproteins perfused into CSF to the mesencephalic floor plate cells. The same authors have found AFRU-positive material attached to choroidal cells in the following situations: (1) rat SCO grafted into lateral ventricle of rat brain (this increases the secretion of material into the CSF) and (2) in vitro co-culture experiments of SCO and choroid plexus explants.…”
Section: Assembly Of Secretory Materials Released By Grafted Scosmentioning
confidence: 99%